2002
DOI: 10.3133/ofr02189
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Element Mines, Deposits, and Occurrences

Abstract: The rare earth occurrences were initially classified into the following deposit types: carbonatites, carbonatites with residual enrichment, alkaline igneous complexes, hydrothermal iron-oxide deposits, deposits hosted by metamorphic rocks, shoreline placer deposits, alluvial placer deposits, paleoplacers, ion adsorption weathering crusts, phosphorites, uranium deposits, and "Other", a miscellaneous and unkown deposits category. To decrease the number of deposits classified as "Other", the following categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 6 publications
1
64
0
2
Order By: Relevance
“…SEM examination indicated that many of these were framboids so were excluded. The other spherules exhibited surface microstructures indicative of rapid melting and quenching as described by previous researchers (25)(26)(27). Spherule sizes at TPR range from 25 to 45 μm, averaging approximately 30 μm, and they are geochemically and morphologically similar to YDB spherules extracted from the other two sites.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…SEM examination indicated that many of these were framboids so were excluded. The other spherules exhibited surface microstructures indicative of rapid melting and quenching as described by previous researchers (25)(26)(27). Spherule sizes at TPR range from 25 to 45 μm, averaging approximately 30 μm, and they are geochemically and morphologically similar to YDB spherules extracted from the other two sites.…”
Section: Resultsmentioning
confidence: 59%
“…Differences in iron abundances account for the dark and light portions of the patterned interior. EDS analysis revealed an elemental composition rich in REEs including lanthanum (10%), cerium (20%) with trace amounts of praseodymium and neodymium, which are not typical elemental components of surficial rocks in the Maryland region (27). Although this unusual spherule may be an atypical anthropogenic contaminant, REEs are also well-known constituents of cosmic material, especially chondritic meteorites (28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…There are about 851 rare earth deposits all over the world that have been discovered or reported, but most of them remain at the first step: the discovery of the occurrence of the resource, while the tonnage and ore grade of these deposits have not been identified; only a small part of these deposits have sufficient geology exploration, and just several deposits have gone into the production stage [28]. The rare earth supply disruption in 2010 promoted companies and governments to explore the global rare earth resources and, consequently, many new deposits have been discovered and explored in this process.…”
Section: Global Potential Of Rare Earth Resourcesmentioning
confidence: 99%
“…Erosion or weathering of primary types may produce deposits, such as placer and ion adsorption deposits [20]. In this paper, based on the USGS classification [21,28,29], we split rare earth deposit types into carbonatite, alkaline igneous rock, placer, ion adsorption, iron-oxide copper-gold (IOCG) deposits, and others. In general, rare earth deposits associated with alkaline igneous rocks are of rather low grade, but may exist in large tonnage and relatively enriched in the HREE, such as Lovozero in Russia (containing 6.6 megaton (Mt) REO at 1.12%) [30].…”
Section: Identification Of Global Rare Earth Resourcesmentioning
confidence: 99%
“…Richardson and Birkett (1996a, b) provided excellent descriptions of carbonatite and peralkaline associated deposits with an emphasis on Canadian occurrences. Orris and Grauch (2002) presented a worldwide compilation of data on rare earth deposits and occurrences. Berger and others (2009) compiled tonnage and grade data for Nb-and REE-bearing carbonatite deposits.…”
Section: The Rare Earth Elementsmentioning
confidence: 99%